The extent of Arabic language teachers’ awareness of the importance of modern teaching methods in education and their practice of them - مطيلب, هبة عليوي (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Research Abstract The current research aims to identify the extent of awareness of teachers of the importance of modern methods of learning and the extent of their practice, and the researcher adopted an important approach called descriptive and a questionnaire consisting of (20) points, and made sure of its sincerity and stability, the sample consisted of teachers and teachers of the Arabic language were selected in a random way, and the questionnaire was analyzed by the program (spss) and the researcher reached the need for Arabic language teachers to training to identify the importance of modern methods in education, Where their needs were medium and on the basis of the results that were reached, the researcher recommended the following: 1. Conducting workshops and training courses for teachers in all disciplines to qualify them to use modern teaching methods. 2. Directing teachers to the need to use modern teaching methods to achieve the desired goals. 3. The need to provide modern teaching techniques in remote schools by the Directorate of Education of Babylon.